Who cares about stock market booms and busts? Evidence from data on mental health - Anita Ratcliffe; Karl Taylor (Institute for the Study of Labor (IZA), 2012)
This paper investigates the relationship between share prices and mental health, exploiting the availability of interview dates in the British Household Panel Survey to match the level and changes in the FTSE All Share price index to respondents over the period 1991-2008. We present evidence that the level, 6 month and yearly changes in the share price index are associated with better mental health while greater uncertainty, as measured by index volatility, is associated with poorer mental well-being. Finally, using several proxies of investor status, we find little evidence that this relationship is confined to holders of equity based assets, suggesting that the observed relationship does not arise via wealth effects. Instead, it appears as though share prices matter to mental health because they perform the role of economic barometer.
Keywords: J26; D12; 330; share prices; economic conditions; mental health; Börsenkurs; Wirtschaftslage; Psychische Störung; Zufriedenheit; Großbritannien